Wernicke-Korsakoff Syndrome following Small Bowel Obstruction - Shoumitro Deb; Richard Law-Min; David Fearnley (Behavioural Neurology)
We report a case of a 64-year-old lady who developed clinical features of Wernicke-Korsakoff syndrome following a laparotomy for small bowel obstruction. Following the operation she developed paralytic ileus and required total parenteral nutrition for one month. A suspected history of average 40 units of weekly alcohol consumption prior to the operation could not be confirmed and the patient did not show any sign of alcohol dependence. Within a few months of treatment with a daily oral dose of thiamine 200 mgs supplemented by multivitamins the patient showed subjective evidence of improvement in confusion, confabulation, and anterograde amnesia, although objective tests showed residual deficits in many areas of cognitive functioning, including immediate and delayed recall of verbal and non-verbal materials, planning and switching of attention.